Labeling analysis, organoleptic and physicochemical characteristics of non-alcoholic ginger kombuchas marketed in the metropolitan region of Belém-Pará (Research, Society and Development, 2022)
Kombucha is a sweet and slightly acidic drink consumed around the world and has been gaining popularity in Brazil due to its health benefits, and it can be made from the most varied raw materials. In this context of high popularity, the study aimed to analyze the label, the physicochemical and organoleptic characteristics of non-alcoholic ginger kombuchas marketed in the metropolitan region of Belém and compare the results with other authors and with the current legislation. Two samples of organic ginger kombuchas from different brands, with an alcoholic percentage lower than 0.5%, were acquired in a health products store in Belém, Pará, and sent in specific containers to the Bromatology laboratory of Escola Superior da Amazônia (ESAMAZ) to carry out label analysis (whether it contained the name of the plant species, aroma, alcohol and prohibited expressions), organoleptic analysis (before opening and after opening the bottle); and physicochemical (pH, soluble solids, density, total titratable acidity, alcohol and protein content), and all analyzes were performed in triplicate. The results obtained from the label were consistent with those recommended by current legislation, as well as the organoleptic and physical-chemical examinations. Therefore, it is evident that the analyzed samples are in accordance with the quality and identity standard established by Organs responsible bodies.